Disentangling food-web environment relationships: A review with guidelines - Mestre, Frederico; Gravel, Dominique; García-Callejas, David; Pinto-Cruz, Carla; Matias, Miguel G.; Araújo, Miguel B. (Basic and applied ecology, 2022)
•We reviewed the literature of the last decade on food web ecology.•The diversity of approaches, scales and study objectives prevent synthesis.•Progress requires theory refinement and standards for data and methods.•Geographically distributed empirical and experimental studies are also required. Food webs represent the energy fluxes and the nutrient cycling between interacting species that underpin several ecosystem functions. Whether and how interactions vary across environmental gradients is still largely unknown. We reviewed the literature searching for systematic relationships between structural food-web properties and environmental gradients. Temperature and biotic factors are amongst the most frequently addressed drivers of food-web structure. We also assessed the degree to which food-web ecology has accomplished a mechanistic understanding of ecosystem functioning. We found that most studies are one-off descriptions of local food webs making it difficult to achieve an understanding of the response to human or environmental gradients. The lack of a consistent theory predicting how food webs change across environmental gradients, the diversity of objectives in food-web studies, and the absence of a standardized methodology for analysing them severely limit progress in the field. Moving forward requires the establishment of a core set of testable predictions, agreed standards for data collection and analysis, and the development of geographically distributed experimental studies of food-web dynamics.